An Architecture of the Whole. - SADLER, SIMON (Journal of Architectural Education, 2008)
This article offers a history and theory of “whole design” as it emerged through countercultural ecology, by offering a critical reading of the Whole Earth Catalog and its affiliate publications, and correlating it with design projects and related philosophies from the 1960s to the present day. The article proposes that the Catalog was itself a sort of architecture, a colloquium connecting its participants to design and to the world at large. Despite its determinist, systems-based origins, the article suggests that whole design harbored an ideologically and aesthetically vibrant indeterminism of continuing relevance to sustainability.